Cloud computing in the field of education (International Journal of Engineering and Computer Science, 2017)
Cloud computing is also known as “on-demand Computing”, is use for sharing Data, Resources and Information. Cloud computing has now become a highly demanded service. Cloud Computing is one of the important and popular internet computing. It emerges as a new computing paradigm which aims to provide reliable and customized computing environments for end-users. From the past few years, there has been a rapid progress in Cloud Computing. Today's IT professionals in educational institutions need to respond quickly to increasing demands from students and faculty, while coping with fixed or declining budgets and staff. In this challenging environment, cloud-based computing has become an increasingly attractive option for delivering education services more securely, reliably, and economically. In today’s higher education environment, IT organizations must keep pace with a long list of competing demands. This paper has discussed the concept of Cloud Computing in education and on the basis of this issue analyzes its impact and advantages in the field of education.